ANALISIS PENGARUH HARGA MINYAK DUNIA DAN HARGA EMAS DUNIA TERHADAP INDEKS HARGA SAHAM GABUNGAN DI BURSA EFEK INDONESIA - Maria Ariesta Utha (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2015)
This research analysed the ittfluence of crude oil price, gold price, and exchange rate toward composite index in Indonesian Stock Exchange. Dependent variable of this reseach is composite index and independent variable of this research are crude oil price, gold prke, and exchange rate. This Research by using time series data on period 2010-2014. The Method of this research is multiple linier regression. To get unbiased model, in this research used classical assumption test. Result of this research indicate that crude oil price and gold price have not significant influence toward composite index and exchange rate have significant influence toward composite index. Based on determination test result crude oil price, gold price, and exchange rate have simultant influence toward composite index.